Model of Archeological and Cultural Heritage Tourism Route Management for Driving Economic Community at Upper Mun River - Tanapiboonpong, Chitsanupong; Thopon, Jirapat; Ekkasart, Ekkarat (Journal of Management Science Nakhonratchasima University, 2025)
This research aimed to 1) study the potential of tourism resources, 2) create tourism routes, and 3) develop a management model for archaeological and cultural heritage tourism routes. The target area comprised 6 locations, and the target group comprised 5 groups. Data collection tools included evaluation forms, questionnaires, and interviews. Data analysis employed descriptive content analysis and quantitative analysis using statistics such as frequency, percentage, mean, and standard deviation. The results showed that the overall potential of archaeological and cultural tourism resources in the upper Mun River basin was high, with a mean score of 4.02. Tourism attractiveness had the most significant potential. Regarding the creation of archaeological and cultural tourism routes in the upper Mun River basin, two programs were proposed: a one-day tour program, or the "2 Stones" route, encompassing tourism in two sub-districts: Hin Dad and Hin Khon; and a two-day tour program, or the "2 Stones, 4 Castles" route, encompassing tourism in Hin Dad and Hin Khon sub-districts, connecting with tourist attractions within Nakhon Ratchasima province, as well as connecting Nakhon Ratchasima and Buriram provinces. The research also included a model for managing archaeological and cultural heritage tourism routes, as well as a community-based tourism management approach that adheres to safety guidelines in tourist areas, encompassing planning, implementation, monitoring, and continuous development.